Supply Chain And Development Strategy Of Virgin Coconut Oil (Vco) CV. Aji Saka Kelapa - Wardani, Fira Dwi; Puryantoro; Suryaningsih, Yasmini (JURNAL AGRIBISAINS, 2025)
Supply chain analysis and development strategy of Virgin Coconut Oil (VCO) at CV. Aji Saka Kelapa is needed to determine the flow of products, finances and information in order to meet consumer demand spread throughout Indonesia. Thus, it is expected that producers can be more effective and efficient in marketing vco production. This study aims to: (1) Identify the structure and analyze the vco supply chain at CV. Aji Saka Kelapa in Sumberejo Village, Banyuputih District, Situbondo Regency. (2) Analyze the development strategy of vco at CV. Aji Saka Kelapa in Sumberejo Village, Banyuputih District, Situbondo Regency. The population in this study were farmers, directors, managers, retailers, and end consumers. The sampling technique used in this study was Snowball Sampling. The sample of this study amounted to five respondents, the sample was obtained from 1 farmer, 1 director, 1 manager, 1 retailer, 1 consumer. The types of data used are primary data from questionnaires, observation techniques, interviews, documentation and secondary data. Data was processed and analyzed to determine the supply chain pattern using Snowball Sampling while to determine the VCO development strategy at CV. Aji Saka Kelapa using the swot analysis method. The results showed that the supply chain at CV Aji Saka Kelapa starts from farmers to the VCO processing industry to distributors, to retailers, and consumers. The VCO development strategy at CV Aji Saka Kelapa is in quadrant I (progressive) which supports aggressive strategies.